“It was obscene in the real world”: La funzione del linguaggio scortese di Jordan Belfort in The Wolf of Wall Street (2013) - Rossi, Valentina (Testo e Senso, 2024)
The present contribution analyses language as performed in The Wolf of Wall Street (2013) from a pragmatic perspective. More specifically, by focusing on the utterances spoken by Jordan Belfort, the protagonist of the movie, this study aims to demonstrate how impoliteness qualifies as an intrinsic feature of his speeches from a certain point in his story, as he constantly performs it regardless of the context in which he operates. This article is structured into two sections: the former outlines the methodology; the latter delves into Belfort’s language as displayed during his early days as a connector and when he becomes the Wolf of Wall Street, an accomplished stockbroker.